Variably rotated lamproite dikes within a transpressive fault zone: Structural and paleomagnetic analysis of the Socovos Fault zone (Eastern Betics, SE Spain). (December 2022) - Pérez-Valera, Luis Alfonso; Villalaín, Juan José; Pérez-Valera, Fernando; Azor, Antonio; Sánchez-Gómez, Mario
Abstract: Rotations of large-scale crustal blocks deduced from paleomagnetism are usually invoked to support evolutionary tectonic models in orogens. However, the regional representativeness of local paleomagnetic rotations strongly depends on the structural context and can lead to conflicting results. This work analyzes an unusual cluster of almost coeval lamproite dikes (9.3–7.1 Ma) intruded along a 25 km-long segment of the Socovos transpressive fault zone in the Eastern Betics, with a view to determine rotations at the metre-scale. This fault zone has contrasting deformation styles, depending on the rheology of the rocks, which vary from ductile evaporites (gypsum) to brittle carbonates. The volcanic and subvolcanic rocks present a primary acquisition of high quality natural remanent magnetization, which defines a single directional component with very narrow α95. Matching the outcrop scale structures with the apparently dispersed paleomagnetic directions in the fault zone allows us to differentiate four deformational domains with distinctive characteristics: (1) a brittle zone with deformation concentrated in planes that bound blocks with no rotation or rotations below the expected secular variation ( ± 16° in inclination and ± 21° declination); (2) transpressive decametre-scale duplexes or single horses, also limited by brittle faults, where inclined axis rotations below 60° occur as rigid blocks; (3) buckling folds in ductile units associated with local reverse faulting; and (4), a triclinic transpressive ductile shear zone affecting a gypsum layer, where volcanic boudins have a rotation that is the sum of folding parallel to the shear zone walls plus an angular shear of 36°. These paleomagnetic results indicate that fault displacement continues after 7 Ma with the same kinematics as previously. Besides regional findings, this study illustrates the potential usefulness of small-scale paleomagnetic analysis for determining strain partitioning and deformation mode along large and complex transpressive fault zones, as well as the necessity to know the local structure to attribute regional meaning to the paleomagnetic rotation data. Highlights: Metric-scale block rotations are analyzed using paleomagnetism on a transpressive fault. 9.3–7.1 Ma lamproite volcanic dikes present high quality remanent magnetization. Brittle and ductile structures coexist in the transpressive fault zone after intrusion. Structure and paleomagnetic rotations allow defining four deformational domains. A combination of rotations is recognized in a triclinic transpressive ductile shear zone.